Features of diet in patients with cardiometabolic diseases with gout and hyperuricemia: A review - Margarita A. Gromova; Vladimir V. Tsurko; Antonina V. Starodubova; Oxana A. Kislyak (Терапевтический архив)
Gout, like hyperuricemia, is often associated with serious cardiometabolic and renal comorbidities that lead to persistently elevated rates of premature mortality in the population. Traditional dietary recommendations given to patients to prevent purine load require revision. This article holistically reviews the relevant scientific rationale and available evidence to provide evidence-based dietary recommendations for the prevention and treatment of hyperuricemia and gout and its cardiometabolic comorbidities.